Radiation Dose Evaluation for Radiotherapy Workers at Unand Hospital Using Four-Element Thermoluminescence Dosimetry - Fardela, Ramacos; Milvita, Dian; Rasyada, Latifah Aulia; Almuhayar, Mawanda; Diyona, Fiqi; Mousa, Almahdi (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2023)
Radiotherapy is a non-surgery therapy that employs ionizing radiation like X-ray or even radiation to cure cancer as a curative activity. Radiation dose rate analysis is required for the person who worked on radiotherapy to strengthen safety precautions for radiation protection, notably in oncology radiation. The research attempted to disclose time trends and radiation dose rate exposure variations among personnel in radiotherapy installation. Radiation dose examination utilizing four-elements TLD received from 16 respondents grouped into six groups (radiation oncologist, medical physicist, radiotherapist, electromedicine, nurse, and sculptor). The number of occupancy exposures rose 55.5% from 2018 to 2022. The most significant annual radiation dose rate for 900 patient workloads attained by medical physicists was 0.996 mSv. In addition, electronics receive the lowest annual radiation dose at Unand Hospital. Annual effective dose exposure by radiation is still safe, below national or international regulations. However, a protective improvement process is vital to limit radiation interaction, particularly for medical physicists, who are the most vulnerable to radiation exposure.